Public History and School International Perspectives - Demantowsky, Marko (De Gruyter, 2018)
How do schools and public history influence each other? Cases studies focusing on school and public history around the world shed light on the intricate relationships between schools, students, teachers, policy makers and public historians. From why Robben Island is not included in South African curriculum to how German schools shape Holocaust memory, the case studies offered in this book sheds light on a current topic.